Exercising in times of COVID-19: what do experts recommend doing within four walls? - Rodriguez, M. A.; Crespo, I.; Olmedillas, H. (Revista Espanola de Cardiologia, 2020)
In conclusion, the most representative institutions in terms of physical exercise and health have created spaces and recommendations to encourage people to continue to be physically active during the lockdown. The population should perform multicomponent full-body programs including aerobic, strengthening, balance, and stretching exercises. Furthermore, cognitive tasks are strongly recommended in the elderly to preserve cognitive ability and brain activity